Between conflation and denial – the politics of climate expertise in Australia. Issue 1 (2nd January 2019) - Tangney, Peter
ABSTRACT: Scientific warnings about impending climate disaster and experts' advocacy for more and better climate science have been largely unsuccessful for advancing evidence-based policy in Australia. Continuing expectations to the contrary stem from a reliance on the supposed ability of science to prime political understandings of climate change. This paper shows how scientists undermine this 'deficit model' ideal by conflating types and uses of evidence and expertise in policymaking. These tactics are unconvincing for conservative opponents, for whom climate science is far from the last word on what climate change means. This paper examines experts' rhetorical tactics through the eyes of conservative policymakers and, thereby, proposes a strategy more likely to effect resilient climate adaptation and mitigation policies in Australia.